フジ コウロ (1979-1980) ニ オケル ヒョウメン カイスイ チュウ ノ クロロフィルα リョウ ノ ブンプ - 谷村, 篤; タニムラ, アツシ; Tanimura, Atsushi (1981)
P(論文) 1979年11月から1980年4月の間, 第21次南極地域観測隊の海洋生物定常観測の一環として「ふじ」航路に沿って, 表面海水中のクロロフィルα量の測定を行った。調査地点は, 216点である。クロロフィルα量の高い値は, セレベス海, マカッサル海峡, マラッカ海峡の陸地に近い海域および南極海域で見い出された。南極海域のクロロフィルα量は, 0.06～2.89mg/m^3と大きな変動を示し, とりわけ, 収束線域および大陸沿いの浮氷域で顕著であった。今回, フリマントル出航後, 東経110度線に沿って南緯60度まで2時間おきの表面観測を行い, クロロフィルα量の変動状態を従来より明確に知ることができた。しかし, クロロフィルα量と海洋環境の関わりについては必ずしも明らかではなく, 今後さらに密な観測を行うことが望まれる。 The measurements of chlorophyll α concentration in the surface sea water were carried out at 216 stations along the route of the icebreaker FUJI from November 1979 to April 1980. This observation was conducted as a part of the routine works of marine biological program of the Japanese Antarctic Research Expedition (JARE). The geographical distribution of chlorophyll α resembled the results obtained by the previous JARE investigators. High chlorophyll α concentrations were observed in the Southern Ocean and also in the areas adjacent to the landmass. In the Southern Ocean, the chlorophyll α concentration fluctuated from 0.06mg/m^3 to 2.89mg/m^3. The chlorophyll α was high and fluctuated particularly near the Subtropical Convergence, the Australasian Subantarctic Front, the Antarctic Convergence and in the pack-ice region along the Antarctic coast. To study the distribution of chlorophyll α and its correlation to the oceanographical conditions, a two-hour interval observation was carried out from 34°S and 60°S along 110°E on the southward leg. The more detailed information on chlorophyll α distribution was obtained, although the data are still insufficient to explain clearly the relation between them. departmental bulletin paper